(untitled) (Journal of Medicine, 2019)
Introduction: Modern management of bronchial asthma requires prolonged medications to prevent symptoms and airflow limitations. An important issue in proper management of bronchial asthma is adherence to treatment. Objective: To see the non-adherence rate to inhalational medication in bronchial asthma patient as well as to see the factors responsible for non-adherence. Materials and Method: It was a cross sectional study conducted from 1st September 2017 to 31st March 2018 in Medicine unit of Sir Salimullah Medical College and Hospital (SSMCH). Result: Among the 136 respondents 70% were male and 30% were female. Non adherent rate was 93.7% for male and 100% for female. High cost of medicine, poor counseling, lack of family support, lack of immediate efficacy, forgetfulness, knowledge on how to use device are the main factors for non-adherence. Conclusion: The rate of non-adherence is very high amongst the participants. Therefore promoting optimal medication adherences through education, proper counseling is essential to optimize the benefits of treatment J MEDICINE JAN 2020; 21 (1) : 41-45